Perfluorosulfonated ionomers membranes: Melt‐processing and characterization for ion exchange applications. Issue 4 (30th September 2013) - Tang, Weihua; Zhang, Rui; Liu, Beibei; Yuan, Huilin
ABSTRACT Perflurosulfonated ionomers membranes with different ionic‐exchange capacity were successfully fabricated via melt‐extruding and casting of their –SO2F precursors. A systematical investigation of the thermal stability, crystallinity, and rheological properties of the precursors was performed to secure their optimized processing conditions. The tensile properties of acid‐form membranes are found to increase with base‐hydrolysis time, where a tensile strength of 38.2 MPa is readily obtained after 24 h's base‐hydrolysis. The content of –SO2F or –SO3H containing side‐chains plays an important role in the thermal stability, rheological, and mechanical properties of the precursor or the acid‐form membranes. The strong ionic interactions, attributed to the –SO3H groups, lead to decreased crystallinity and tensile strength for different IEC membranes. The acid‐form membranes exhibit good proton conductivity and low methanol crossover in comparison with reference Nafion membrane. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39944.